2017
DOI: 10.1097/scs.0000000000003926
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Neurophysiologic Monitoring for Prediction of Postoperative Neurological Improvement in a Child With Chiari Type I Malformation

Abstract: The authors' data provides 1 possible interpretation of INM for safety aspect, but also which degree of decompression in each patient will require. The improvement in MEPs and SSEPs observed during decompression procedure may be a good indicator for the prediction of the clinical improvement seen postoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…These should not be considered firstline examinations and their role in the diagnosis and evaluation of CM1 is unproven. Additionally, in spite of their utility in case of brainstem or spinal cord involvement, their role in the intraoperative monitoring at the moment of positioning and during the posterior fossa decompression remains controversial [ 41 , 42 ]. Polysomnography is indicated to confirm the diagnosis of sleep apneas at any age, in particular in infants and small children with significant overcrowding of the posterior fossa.…”
Section: Resultsmentioning
confidence: 99%
“…These should not be considered firstline examinations and their role in the diagnosis and evaluation of CM1 is unproven. Additionally, in spite of their utility in case of brainstem or spinal cord involvement, their role in the intraoperative monitoring at the moment of positioning and during the posterior fossa decompression remains controversial [ 41 , 42 ]. Polysomnography is indicated to confirm the diagnosis of sleep apneas at any age, in particular in infants and small children with significant overcrowding of the posterior fossa.…”
Section: Resultsmentioning
confidence: 99%
“…Another important aspect provided by intraoperative monitoring concerns variation on motor and somatosensory evoked potentials' curves. Kawasaki Y, et al have found improvement in the potentials' curves during decompression in Chiari type I malformation decompressive surgery as a good indicator for clinical recovery [32]. We believe that this knowledge could also be useful during skeletal C0-C1 decompression surgery from skeletal dysplasia with foramen magnum and upper cervical stenosis.…”
Section: Discussionmentioning
confidence: 60%
“…15,17 Some show that IONM may be useful to determine the efficacy of decompression, assess the risk of neurological injury, and prevent complications from manipulation of the craniocervical junction. 15,18,19 The association between radiologic imaging of CM-I patients and IONM findings is inconsistent. One study found no relationship between the extent of CM-I tonsillar ectopia and intraoperative brain stem auditory evoked potentials.…”
Section: Discussionmentioning
confidence: 99%